The effect of current on characteristic for welded joint between 316 and 316L stainless steel including microstructure and mechanical properties - Navid Moslemi, 1985-; Norizah Redzuan, supervisor; Fakulti Kejuruteraan Mekanikal (2014)
Thesis (Sarjana Kejuruteraan (Mekanikal - Bahan)) - Universiti Teknologi Malaysia, 2014